Lucubrationes Propertianae - Georg Luck (Exemplaria Classica, 2010)
This article presents some critical notes on the text of Propertius which stem from a reading of the recent edition by Heyworth (Oxford 2007). These personal reflections are the fruit of many years’ contact with the elegies.